Software process improvement and management : approaches and tools for practical development - Fauzi, Shukor Sanim Mohd, 1980-; Nasir, Mohd Hairul Nizam; Ramli, Nuraminah (Hershey, PA : Information Science Reference, 2012)
"This book offers the latest research and case studies on software engineering and development to assist organizations and software engineers in adding a measure of predictability to the software process"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Software engineering -- Case studies